Study the performance of High Voltage Direct Current Transmission using MATLAB - Abed Al-Jashami, Jameel K. (Nahrain University College of Engineering Journal, 2008)
Some of the electric networks adjacent countries are linked to either the alternating current lines or to direct current lines, that is really depends upon the eographic distance of the linking points and the amount of the used current. In view of rapid and huge increasing of electric power consumption and to shorten the value of losses inside transferring operation besides the electric system steady. Accordingly and due to all we have mentioned the direct current transmission has been established in high voltage for long distance. These lines can be used when the linking points are far- off, and when the frequency for the two required systems are different. Therefore transformation stations are being used at both ending sides to transfer from alternating to direct current and vice-versa. Also a (HVDC) system can be constructed according to stages in proportion with the voltage development and the load requirement. There is always the need to maintain the transformation voltage at ultimate possible value in order to have a high efficiency operation. In this paper the transmission line was represented by using MATLAB program for two different lengths (300,600) Km & different firing angles then comparison is held between these two lengths according to efficiency & economical view